The Role of Task Type in Enhancing Writing Fluency: A Study of Saudi Female University Students - Alshehri, Nada (International Journal of Linguistics, Literature and Translation, 2024)
This study investigates the impact of task type on L2 writing fluency among 50 Saudi female university students. Using a mixed-methods approach, the research examines how narrative and argumentative tasks influence syntactic complexity, lexical diversity, and writing speed. The findings reveal that narrative tasks are associated with higher syntactic complexity, while argumentative tasks promote greater lexical diversity. No significant difference was observed in writing speed between the two task types. These results highlight the importance of task selection in language instruction and suggest that a balanced approach, incorporating both task types, can enhance L2 writing fluency. The study contributes to the understanding of task-based instruction in EFL contexts and offers practical implications for curriculum design.